The Effect of Tax Socialization, Superior Service, and Service Quality on Taxpayers’ Satisfaction and Compliance - Sukesi Sukesi; Isroim Yunaidah (Universitas Hayam Wuruk Perbanas, 2019)
The impact of valuable services for taxpayers will increase the aware-ness and compliance of taxpayers. This study aims to explore whether there is a direct or indirect effect on the effectiveness of tax socialization, superior service products, and the quality of services to taxpayer satisfaction and taxpayer compliance. The study was conducted at the East Java Provincial Revenue Agency through 48 motorized vehicle service units, with a purposive sampling set at 426 respondents in the Gresik, Bangkalan, Mojokerto, Surabaya, Sidoarjo and Lamongan regions with 2014 ownership of motorized vehicle years. With SEM analysis, the results of the study stated that there were significant direct or indirect effectiveness of tax socialization, superior service products, and quality of service to taxpayers' satisfaction and compliance as a mediating variable. The implication is that if the Central Tax Office conducts tax socialization effectively on target, provides superior service products, and delivers quality of services in all districts/cities in East Java Province, they will be able to get people to comply by voluntarily paying motor vehicle taxes on time.